Developing teaching materials of leraning cycle 7E based ARCS motivational strategies for topic optical instruments - E Eniswatin; P Prabowo; T Tukiran (International Conference on Mathematics and Science Education of Universitas Pendidikan Indonesia, 2018)
This research aimed to develop teaching materials of Learning Cycle 7E based onARCS motivational strategies for Optical Instruments matter. The research of subjects areteaching materials and students of grade X in MAN Lamongan. the study used Dick and Careymodel. The developed teaching materials is tryouted using one group pretest-posttest design inthe classroom. the study of data analysis used descriptive quantitative technique and descriptivequalitative technique. The result are obtained, developing teaching material validity aregenerally categorized as valid, RPP performing is well, the dominant activity is not observationresult, student also have positive responses to learning model, student learning achievementwhich include competency knowledge with average 0,76 (high gain categorized). the obstaclesencountered during learning is the time required to carry out learning activities exceeds frompredetermained time. Based in the findings and results, it is concluded that the teachingmaterials of Learning Cycle 7E based ARCS motivational strategies are feasible applicationwhich has developed fit to higher of learning achievement.